KEMAMPUAN MENULIS KALIMAT DARI INFORMASI TABEL OLEH SISWA KELAS VII SMP NEGERI 1 KECAMATAN LEMBAH SORIK MARAPI KABUPATEN MANDAILING NATAL - ANNI RAHIMAH (Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to determine the ability to make sentences from table information by students of grade 1 SMP Negeri 1 Kecamatan Lembah Sorik Marapi Mandailing Natal District. The method used in this research is descriptive method. The data collection tool used is the test in the form of assignment that is telling students to write the news sentence effectively based on the table information. From the research result, the ability to make sentences from the table information by the students of class VII of SMP Negeri 1 Kecamatan Lembah Sorik Marapi Mandailing Natal District is quite adequate with score 6. There are three difficulties experienced by students in making sentences from the table information is difficulty pouring ideas, limited vocabulary mastery, and the difficulty of writing sentences effectively using their own language, however, the level of difficulty faced by students is relatively small.